1981
DOI: 10.1017/s0424820100099088
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Galactose-Specific Recognition System of Mammalian Liver

Abstract: The rapid removal of circulating desialylated glycoproteins from the blood plasma of mammals is well-documented, occurs exclusively in the liver and is mediated by a carbohydrate recognition system present only in hepatocytes. After binding to a plasma membrane receptor that recognizes galactose, glucose or N-acetylgalactosamine residues on their oligosaccharide chains, ligands are rapidly internalized, transported within membrane-bound structures to lysosomes and subsequently degraded. The fate of the recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The experiments described above demonstrated that single hepatocytes and cells in monolayer cultures resembled hepatocytes in vivo, both quantitatively and qualitatively, in terms of binding activity, internalization, and fate of ASGPs. We next investigated the distribution of ASGP surface receptors on freshly isolated cells, because these cells have no recognizable blood front domain, the predominant location of the ASGP receptor in situ (6,7) . Qualitatively, the EM-ARG results indicated a random distribution of binding sites over the entire surface .…”
Section: Asor-hrp Cytochemistry In Dissociated Hepatocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments described above demonstrated that single hepatocytes and cells in monolayer cultures resembled hepatocytes in vivo, both quantitatively and qualitatively, in terms of binding activity, internalization, and fate of ASGPs. We next investigated the distribution of ASGP surface receptors on freshly isolated cells, because these cells have no recognizable blood front domain, the predominant location of the ASGP receptor in situ (6,7) . Qualitatively, the EM-ARG results indicated a random distribution of binding sites over the entire surface .…”
Section: Asor-hrp Cytochemistry In Dissociated Hepatocytesmentioning
confidence: 99%
“…The asialoglycoprotein (ASGP) receptor is localized exclusively to the parenchymal cells of mammalian liver and functions in the rapid removal of desialylated glycoproteins from the circulation by receptor-mediated endocytosis (1)(2)(3)(4)(5) . The distribution of the ASGP receptor along the plasma membrane of hepatocytes in situ is restricted to the blood sinusoidal surface and is preferentially concentrated in coated pits present in this domain (6,7) . During the preparation of single hepatocytes by collagenase perfusion of the liver, cells lose the three morphologically identifiable plasma membrane domains (8,9) (sinusoidal, bile canalicular, and lateral surfaces), yet retain the capacity to bind, internalize, and degrade 125 1-ASGPs (10)(11)(12)(13)(14)(15)(16) .…”
mentioning
confidence: 99%
See 1 more Smart Citation